Leaf Pigment Analysis and Spatial Variation in Thalassia hemprichii: A Case Study from Southern Part of Bali Island Indonesia - Ahammed K. K. Basheer; Karang I Wayan Gede Astawa; Yasa Putu Kumara; Krisnanda I Made Dwita; Nuarsa I Wayan; Irfana Kottangodan (BIO Web of Conferences)
Seagrass plays a vital role in marine ecosystems by providing food and shelter, maintaining water quality, protecting the coastline, and maintaining nutrient cycling and oxygen content. However, due to the climate change and tourism activities, seagrass around the world is facing high stress and degradation. Therefore, a systematic study is required to analyse the impact on seagrass. This study aims to analyse stress in the Thalassia hemprichii species in Benoa Bay, Bali, given Bali’s tourism industry and Benoa Bay’s popularity for water sports. Field data were collected at 96 locations, and the leaf samples were analysed for leaf pigments. The study, Chlorophyll-a (Chl-a), chlorophyll-b (Chl-b), total chlorophyll, and total carotenoids were analysed using standard protocols. Total chlorophyll ranged from 0.502 to 1.906 mg/g while the total carotenoids ranged from 0.224 to 1.018 mg/g. The lowest chlorophyll levels were found in tourism hotspots like Sanur and Benoa harbour, while these regions also exhibited higher carotenoid levels. This suggests high stress in these areas, possibly due to high-speed boat traffic. The study could be further improved by quantifying other environmental parameters like water quality and temperature to understand the root causes. However, the study provides baseline information for the conservation of Benoa Bay.